Skrining Fitokimia Daun Tembelekan (Lantana Camara Linn) sebagai Anti-Inflamasi dengan Penghambatan terhadap Denaturasi Protein secara In Vitro - Hasnaeni; St. Maryam; Latifah Al Sadilah (Jurnal Kesehatan Cendikia Jenius, 2024)
The leaves of the tembelekan plant can be used to treat wounds, boils, rheumatism, leprosy, and scabies. This study aims to conduct Phytochemical Screening to determine what secondary metabolites are contained in the extract of the Tembelekan plant (Lantana camara L.) and the anti-inflammatory activity of the tembelekan plant (Lantana camara L.) by inhibiting protein denaturation in vitro. This research was conducted in the Phytochemical Pharmacognosy Laboratory and the Chemistry Laboratory of the Faculty of Pharmacy, Muslim University of Indonesia, Makassar. This research was conducted from March to May 2024. The population in this study was the tembelekan leaf plant (Lantana camara L.), and the sample used was the ethanol extract of tembelekan leaves (Lantana camra L.) obtained from Bulukumba Regency, South Sulawesi Province. This research was conducted experimentally using the phytochemical screening method and the in vitro protein denaturation inhibition analysis method. The results of the study showed that tembelekan leaves contain chemical compounds in the form of flavonoids, tannins, saponins, and steroids. The results of the percentage of inhibition of sodium diclofenac obtained ranged from 25.97% to 83.68%. The ethanol extract samples of tembelekan leaves obtained ranged from 26.04% to 61.82%, which means that the ethanol extract of tembelekan leaves tested had anti-inflammatory activity. In conclusion, the ethanol extract of tembelekan leaves has the potential as an anti-inflammatory agent. It is recommended to conduct further research on the concentration of tembelekan leaf extract (Lantana camra L.)